Fundamentals of Atomic Force Microscopy - Reifenberger, Ronald G. (Singapore : World Scientific Publishing Co. Pte Ltd., 2015)
"The atomic force microscope (AFM) is a highly interdisciplinary instrument that enables measurements of samples in liquid, vacuum or air with unprecedented resolution. The intelligent use of this instrument requires knowledge from many distinct fields of study. These lecture notes aim to provide advanced undergraduates and beginning graduates in all fields of science and engineering with the required knowledge to sensibly use an AFM. Relevant background material is often reviewed in depth and summarized in a pedagogical, self-paced style to provide a fundamental understanding of the scientific principles underlying the use and operation of an AFM. Useful as a study guide to (3z(BFundamentals of AFM(3y(B, an online video course available at https://nanohub.org/courses/AFM1/ Suitable for Graduate/Undergraduate Independent Reading and Research Course in AFM (with the combination of book and online videos)"--s
Part I: Foundations
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web. System requirements: Adobe Acrobat Reader.
Keywords: Atomic force microscopy; Electronic books